2018
DOI: 10.4070/kcj.2018.0231
|View full text |Cite
|
Sign up to set email alerts
|

Left Atrial Appendages Occlusion: Current Status and Prospective

Abstract: Stroke continues to be a major cause of morbidity and mortality in atrial fibrillation (AF) patients. Oral anticoagulation (OAC) provides protection against stroke and peripheral embolization in AF but significant proportion of patients could not be started on anticoagulation because of bleeding complications. Left atrial appendage harbors clot in about 90% of nonvalvular AF. The advent of left atrial appendage occlusion (LAAO) techniques has provided these patients with alternative to OAC for stroke prophylax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 57 publications
0
20
0
Order By: Relevance
“…It went a step further to propose that patients on OAC had better outcomes [11]. However, a study was conducted by Sharma et al that studied different LAAO devices, and their findings showed that LAAO devices were adequate for the prevention of stroke [12]. This study is a review; hence, it has precedence over the previously mentioned case-control study based on the premise that the study has a higher quality of evidence.…”
Section: Figure 1: Safety Concerns With Laao and Oacmentioning
confidence: 98%
“…It went a step further to propose that patients on OAC had better outcomes [11]. However, a study was conducted by Sharma et al that studied different LAAO devices, and their findings showed that LAAO devices were adequate for the prevention of stroke [12]. This study is a review; hence, it has precedence over the previously mentioned case-control study based on the premise that the study has a higher quality of evidence.…”
Section: Figure 1: Safety Concerns With Laao and Oacmentioning
confidence: 98%
“…Left atrial appendage (LAA) occlusion/ligation using one of several devices or surgical techniques has been developed as an alternative to anticoagulation in high‐risk patients with non‐valvular AF 280–282 . The maximum experience has been with the Watchman device (Boston Scientific), which has been found to be non‐inferior to warfarin in patients who are still candidates for short‐term warfarin treatment 283–285 .…”
Section: How To Assess Risk For Adverse Outcomes In Patients With Atrmentioning
confidence: 99%
“…However, there are no one-size-fits-all NOACs, and this also applies to elderly, particularly the vulnerable patients [43]. Furthermore, a significant proportion of geriatric patients cannot be treated with the necessary OAC because of the comorbidities, and in these patients, occlusion of the left atrial appendage may be a valuable choice [44].…”
Section: Atrial Fibrillationmentioning
confidence: 99%